Sellers’ preferences for online shopping platform using fuzzy AHP / Afza Nazihah Masrom - Masrom, Afza Nazihah (2023)
Mostly sellers nowadays are actively selling their products through online shopping platforms since the usage of e-commerce are increased. Many platforms that have been introduced and popular among people in Malaysia such as TikTok, Shopee etc. However, for this study is aimed to help sellers to make decision in choosing the best platform of online shopping that can be used to sell their product. Fuzzy Analytical Hierarchical Process (AHP) were suggested in this study to solve multi-criteria decision-making problems with fuzzy concept. The alternatives that have been chosen to be evaluated are TikTok (A1), Shopee (A2) and Lazada (A3). Those alternatives are evaluated based on seven main criteria: website quality, payment methods, product variety, delivery and guarantee, surrounding influences, experiences and advertisement. Each criterion came along with a few sub-criteria. The results obtained website quality, payment methods and product variety gave a huge impact in choosing the online shopping platforms and the result found that TikTok (A1) is the best platform for sellers in selling their products.